Antigenic response to CT‐P13 and infliximab originator in inflammatory bowel disease patients shows similar epitope recognition. Issue 5 (5th June 2018) - Goncalves, J.; Santos, M.; Acurcio, R.; Iria, I.; Gouveia, L.; Matos Brito, P.; Catarina Cunha‐Santos, A.; Barbas, A.; Galvão, J.; Barbosa, I.; Aires da Silva, F.; Alcobia, A.; et al.
Summary: Aim: To test the cross‐immunogenicity of anti‐CT‐P13 IBD patients' sera to CT‐P13/infliximab originator and the comparative antigenicity evoked by CT‐P13/infliximab originator sera. Methods: Sera of patients with IBD with measurable anti‐CT‐P13 antibodies were tested for their cross‐reactivity to 5 batches of infliximab originator and CT‐P13. Anti‐drug antibody positive sera from treated patients were used to compare antigenic epitopes. Results: All 42 anti‐CT‐P13 and 37 anti‐infliximab originator IBD sera were cross‐reactive with infliximab originator and CT‐P13 respectively. Concentration of anti‐drug antibodies against infliximab originator or CT‐P13 were strongly correlated both for IgG1 and IgG4 ( P < 0.001). Anti‐CT‐P13 sera of patients with IBD (n = 32) exerted similar functional inhibition on CT‐P13 or infliximab originator TNF binding capacity and showed reduced binding to CT‐P13 in the presence of five different batches of CT‐P13 and infliximab originator. Anti‐CT‐P13 and anti‐infliximab originator IBD sera selectively enriched phage‐peptides from the VH (CDR1 and CDR3) and VL domains (CDR2 and CDR3) of infliximab. Sera reactivity detected major infliximab epitopes in these regions of infliximab in 60%‐79% of patients, and no significant differences were identified between CT‐P13 and infliximab originator immunogenic sera. Minor epitopes were localised in framework regions of infliximab with reduced antibody reactivity shown, in 30%‐50% of patients. Monoclonal antibodies derived from naïve individuals and ADA‐positive IBD patients treated with CT‐P13 provided comparable epitope specificity to five different batches of CT‐P13 and infliximab originator. Conclusions: These results strongly support a similar antigenic profile for infliximab originator and CT‐P13, and point toward a safe switching between the two drugs in anti‐drug antibody negative patients. Abstract : Linked Content This article is linked to Pouillon et al and Goncalves et al papers. To view these articles visithttps://doi.org/10.1111/apt.14847 andhttps://doi.org/10.1111/apt.14860 .